Visual Sovereignty in the Posthuman Condition: Technological Mediation and the Pluriversal Reconfiguration of Indigenous Art - JiaoJiao, Wang; HongJi, Miao (Journal of Posthumanism, 2025)
This study explores how local folk art can cleverly use modern technology and thinking to expand the reality platform and rebuild the autonomy of visual presentation in the posthuman context.